Programming immunogenicity of dengue EDIII vaccine antigens using engineered outer membrane vesicles (OMVs) - Srinivas Duvvada; Farhan Ahmed; Rafiq Ahmad Khan; Shaikh Matin Rahim; Saima Naz; Aradhana Mariam Philips; David Putnam; Avery August; Nooruddin Khan (Vaccine: X, 2025)
Dengue is a mosquito-borne viral infection and is more prevalent in the world with no therapeutics and suboptimal vaccine (Dengvaxia) performance against all four serotypes of the dengue virus. Hence, there is an urgent requirement for a non-infectious and non-replicative vaccine candidate that can elicit a balanced and serotype-specific immune response. In this study, we have engineered bacterial outer membrane vesicles (rOMVs) that display EDIII antigens (EDIII rOMVs). The current formulation modulates the expression of costimulatory molecules on antigen-presenting cells (APCs) as well as enhances the uptake and presentation. Subsequently, the EDIII rOMVs elicited a strong antigen-specific polyfunctional response from CD4+ and CD8 + T cells. The robust antibody response was facilitated by a germinal center reaction characterized by high T follicular helper (Tfh) and B cell response levels in the mice that received EDIII rOMVs. Notably, the produced antibodies demonstrated the ability to neutralize all four dengue virus serotypes in an in vitro infection model, indicating its potential role in protective immunity.